Osteogenic Distraction in Complex Mandibular Defect (International Journal of Medical and Surgical Sciences, 2016)
Distraction osteogenesis (DO) is a surgical technique used in the treatment of facial deformities and malformations and also in the treatment of alveolar bone deficiencies. The aim of this paper is to show the case of a patient with partial edentulism in the symphysis area with a severe vertical and horizontal bone deficiency caused by mandibular trauma. At the initial analysis, the patient related a recent history of fracture in symphysis and right angle of the mandible. Treatment had not been entirely succesfull, therefore, after studying the options, we opted for a treatment at different stages: Stage 1, surgery for osteo shynthesis removal, soft tissue preparation and replacement of the posterior margin of mandibular symphysis; stage 2, distraction osteogenesis, performed 3 months after the first intervention and stage 3, distractor device removal and dental implant installation, performed 6 months after the second intervention. We discuss some factors involved in the treatment success.
Keywords: Distraction osteogenesis; dental implants; mandibular fracture